2018
DOI: 10.1589/rika.33.121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Change in Weight Load during Hip Extension and Abduction on Electromyographic Activities of the Gluteus Medius and Maximus Fibers

Abstract: Electromyography (EMG) was used to examine gluteus medius and maximus activities with the hip in sustained extension and abduction. [Subjects and Methods] Subjects were 10 healthy male persons, mean age of 24.4 years. The gluteus medius and maximus overlap area was confirmed with ultrasonic imaging. EMG activity of each muscle was measured during a change in lower limb weight load on the measurement side with the hip in sustained extension and abduction. [Results] Activities of the gluteus medius posterior fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The relationship between the activity of the GMed and the action of the hip joint depends on the direction of the fibrous bundles [2][3][4] . Several studies have reported the effects of rehabilitation exercises on strength in the GMed based on the morphology of fiber bundles [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the activity of the GMed and the action of the hip joint depends on the direction of the fibrous bundles [2][3][4] . Several studies have reported the effects of rehabilitation exercises on strength in the GMed based on the morphology of fiber bundles [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%